Recent advances in addressing the market failure of new antimicrobials: Learnings from NICE's subscription-style payment model - Schurer, Marieke; Patel, Renu; van Keep, Marjolijn; Horgan, Jake; Matthijsse, Suzette; Madin-Warburton, Matthew (Frontiers in Medical Technology, 2023)
BACKGROUND: Antimicrobial resistance (AMR) is a growing threat to global health. With pathogenic bacteria inevitably becoming more resistant to existing antimicrobials, mortality and costs due to AMR will significantly increase over the next few decades if adequate action is not taken. A major challenge in addressing AMR is the lack of financial incentives for manufacturers to invest in developing new antimicrobials. This is partly because current approaches in health technology assessment (HTA) and standard modeling methods fail to capture the full value of antimicrobials. AIM: We explore recent reimbursement and payment frameworks, particularly pull incentives, aimed to address the market failures in antimicrobials. We focus on the ‘subscription-style’ payment model recently used in the UK and discuss the learnings for other European countries. METHODS: A pragmatic literature review was conducted to identify recent initiatives and frameworks between 2012 and 2021, across seven European markets. The National Institute for Health and Care Excellence (NICE) technology appraisals for cefiderocol and for ceftazidime with avibactam were reviewed to evaluate how the new UK model has been applied in practice and identify the key challenges. CONCLUSION: The UK and Sweden are the first European countries to pilot the feasibility of implementing pull incentives through fully and partially delinked payment models, respectively. The NICE appraisals highlighted the complexity and large areas of uncertainty of modeling antimicrobials. If HTA and value-based pricing are part of the future in tackling the market failure in AMR, European-level efforts may be needed to overcome some of the key challenges.